2023
DOI: 10.1097/nrl.0000000000000492
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammation Response Index Predicts Clinical Outcomes in Patients With Acute Ischemic Stroke (AIS) After the Treatment of Intravenous Thrombolysis

Abstract: Background: Intravenous thrombolysis (IVT) is one of the most important means of therapy for patients with acute ischemic stroke (AIS). After cerebral infarction, the inflammatory response fulfills an essential role in the pathobiology of stroke, affecting the process of recanalization. Hence, we evaluated the usefulness of the systemic inflammatory response index (SIRI) for the prognosis of patients with AIS.Methods: A total of 161 patients suffering from AIS were retrospectively analyzed. SIRI was introduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The systemic inflammatory response index (SIRI, SIRI = neutrophils × monocytes/lymphocytes) was also an important prognostic factor for functional outcome in AIS. Chen et al found that SIRI ≤2.54 × 10 9 /l at admission was an independent predictor of good prognosis after intravenous thrombolytic therapy [ 36 ], while other studies confirmed that SIRI at admission was significantly associated with 3-month all-cause mortality [ 38 ]. These findings suggested that SIRI was also an effective prognostic marker.…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%
“…The systemic inflammatory response index (SIRI, SIRI = neutrophils × monocytes/lymphocytes) was also an important prognostic factor for functional outcome in AIS. Chen et al found that SIRI ≤2.54 × 10 9 /l at admission was an independent predictor of good prognosis after intravenous thrombolytic therapy [ 36 ], while other studies confirmed that SIRI at admission was significantly associated with 3-month all-cause mortality [ 38 ]. These findings suggested that SIRI was also an effective prognostic marker.…”
Section: Effect Of Blood Biomarkers On Prognosis Of Aismentioning
confidence: 99%